Methodological Approach to Developing National Differentiated Training in Integrated Border Management in Eastern Partnership Countries - Varga, János; Kupriyenko, Dmytro; Mironau, Dzmytriy; Gáspár, Zsolt (Magyar Rendészet, 2015)
Today the concept of Integrated Border Management (IBM, established in 2002) is a system that contains all the aspects of border guarding. It has also been included in the public administration of the countries of the Eastern Partnership. The exchange of experience related to the specific methodology applied in its teaching has just begun, during which Hungarian, Ukrainian and Belarussian teachers of border guarding examined how to ensure that the staff involved in IBM in Eastern Partnership countries acquire the competences according to a uniform concept and to the necessary extent. They proposed that national differentiated training programmes for the teaching of IBM should be developed and recommended methodologies to be applied in it. The outcome of the exchange of experience is published in the scientific periodicals of the authors’ higher education institutions, in English (in Budapest), in Ukrainian (in Kiev) and in Russian (in Minsk).